2008
DOI: 10.1128/mcb.00874-08
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 7 Promotes PML Sumoylation and Is Essential for PML Nuclear Body Formation

Abstract: Promyelocytic leukemia protein (PML) sumoylation has been proposed to control the formation of PML nuclear bodies (NBs) and is crucial for PML-dependent cellular processes, including apoptosis and transcriptional regulation. However, the regulatory mechanisms of PML sumoylation and its specific roles in the formation of PML NBs remain largely unknown. Here, we show that histone deacetylase 7 (HDAC7) knockdown reduces the size and the number of the PML NBs in human umbilical vein endothelial cells (HUVECs). HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 50 publications
2
62
0
1
Order By: Relevance
“…The deacetylase activity in HDAC7 is known to be relatively weak (61), and it is therefore likely that the protein has additional enzymatic and/or nonenzymatic functions critical in repression, which are yet to be discovered. One possibility is that its recently described Sumo E3 ligase activity (18,23) might play a role in ER␣ given that posttranslational modification by sumoylation is primarily associated with transcriptional repression (48). Future studies will address this question by testing whether HDAC7 can mediate sumoylation of ER␣, which has previously been shown to be sumoylated (62,71).…”
Section: Discussionmentioning
confidence: 99%
“…The deacetylase activity in HDAC7 is known to be relatively weak (61), and it is therefore likely that the protein has additional enzymatic and/or nonenzymatic functions critical in repression, which are yet to be discovered. One possibility is that its recently described Sumo E3 ligase activity (18,23) might play a role in ER␣ given that posttranslational modification by sumoylation is primarily associated with transcriptional repression (48). Future studies will address this question by testing whether HDAC7 can mediate sumoylation of ER␣, which has previously been shown to be sumoylated (62,71).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, class I HDACs interact with PML and this interaction is required for the transcriptional repression function of PML. 39,40 In addition, class IIa HDACs -HDAC4, HDAC5, and HDAC7 -increase PML sumoylation in an acetylationindependent manner, 41 and although it is not clear exactly how HDAC4 and related members positively regulate the sumoylation levels of PML, a putative SUMO E3 ligase activity has been suggested. 42 PML has an inhibitory effect on virus infections in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro deacetylation assays also demonstrated that class IIa HDACs possess potent deacetylase activity (31). Recently, we along with other labs have demonstrated that class IIa HDACs, including HDAC4 and HDAC7, are able to potentiate sumoylation of a variety of proteins including PML, LXR, MEF2, and HIC1 (19,25,(32)(33)(34). In this study, we show for the first time that HDAC7 binds FLNB in a ubiquitination-dependent manner.…”
Section: Discussionmentioning
confidence: 61%
“…Expression plasmids for hemagglutinin (HA)-HDAC5 and -HDAC7, constitutively active CaMK I, green fluorescent protein (GFP)-HDAC7, glutathione S-transferase (GST)-HDAC7, HAubiquitin (Ub), FLAG-Ub, and the myocyte enhancer factor 2 (MEF2)-driven reporter construct have been previously described (19)(20)(21). HDAC7 constructs were generated from mouse cDNA.…”
Section: Methodsmentioning
confidence: 99%